Kajian demokrasi di Indonesia: Media sosial sebagai ruang partisipasi generasi Z - anshor, khula fatul (Maliki Interdisciplinary Journal, 2026)
Digital technology has transformed political participation in Indonesia, particularly among Generation Z (born 1997–2012). Social media has evolved into the primary public space for political expression, civic identity, and democratic engagement among young citizens. This study explores how social media functions as a democratic participation space for Generation Z within the Indonesian political context, employing a qualitative literature review methodology synthesizing ten scholarly sources. Core references include Suciati and Nuqul (2024) on political identity formation via social media; Slamet et al. (2009) on structural barriers to e-democracy in Indonesia; and Faslah (2024) on national identity as a foundation for sovereignty. Supporting sources address Gen Z political participation, Pancasila-based democratic strengthening, digital politics, and civic engagement. Findings reveal that social media operates dually expanding youth political access while simultaneously generating polarization, disinformation, and digital harassment risks. The study concludes that meaningful democratic participation among Generation Z requires the convergence of digital literacy, sound e-democracy policy, and a strong national identity as a moral compass.